A simple dilation-recompaction model for hydraulic fracturing. (December 2016) - Huang, Xuemin; Wang, Jingyi; Chen, Shengnan (Nancy); Gates, Ian D.
Highlights: Key enabler for tight oil and gas production is hydraulic fracturing. Fracturing models tend to be either fast and simplistic or slow and complex. Dilation-recompaction model is a dynamic fracturing approach. Dilation-recompaction model provides reasonable matches to field data. Abstract: Production of unconventional oil and gas resources has played a significant role on the global energy supply, of which tight oil and gas reservoirs are drawing greater focus. The key enabler behind tight oil and gas production has been multi-stage hydraulic fracturing along extended reach horizontal wells. Despite many advances in multistage fracturing, it still remains unclear how to model the hydraulic fracturing process to provide the basis to optimize and predict the properties of fracture networks and associated enhancement of fluid production. In typical reservoir simulation practice, the conventional way to represent the hydraulic fracture is to place high permeability planes around the horizontal well – this means that the user has prescribed the orientation and length scale of the fracture before the simulation has started. In the research documented here, we explore a dynamic fracturing approach that uses a dilation-recompaction model in a reservoir simulator to model hydraulic fracturing. The key strength of the approach is that the geometry and length scale of the fracture is not prescribed a priori. The results of the simulation show that dilation-recompaction model is capable of modeling the hydraulic fracturing process prior to the flow-back and production. The oil, gas, and water rates of the model are well matched to the field data and the extent of the fractured zone predicted by the model is reasonable.